"Prantá feijão", um falar rural nas vicinais de Rorainópolis - Pereira, Nariene do Nascimento (2016)
In dealing with the Portuguese language, all linguistic varieties are effectively relevant, in the sense that there is no language that is inferior to another. As a result of Brazil being a country in which a mixture of peoples, regional and socio-cultural differences is present, it is not possible to speak of a homogenous language. It is in this scenario that we situate Rorainopolis, located in the southern region of the State of Roraima, a relatively new town, made up of migrants encouraged to come to this region as a result of settlement projects. Based on this reality, and by virtue of the scarcity of scientific work on variations of Portuguese in the North of the country, especially in rural zones, we were motivated to observe the speech of residents of that municipality. As such, our research question was formed along the following line: can the speech in the rural zone of the municipality of Rorainopolis be recognised as a characteristic of the North even though its residents are originally from other states of the country? The principle objective of the research is to contribute to sociolinguistic studies of the North, seeing that few works have yet been done in this thematic area in the region. In relation to the methodology and theoretical framework, the research approaches the issue from a sociolinguistic viewpoint, which methodologically favours analysis of the body in interview format. The most noteworthy sociolinguistic developments encountered were the social variables: origin, age and educational level. With regard to the linguistic variations, the highlight occurs on the syntactic level, with the use of the term a gente (literally people) as an indetermination of the subject, the non flexion of number in nouns, quantifiers and verbs. On the morphological level, we focused on the gerund and the weakening of the (r) in the coda position. The rural zone as a rule is distanced from urban sectors and is on many occasions dispersed; however, this did not prevent us from substantiating certain occurrences of rural speech common to those residents, although they originated from different regions of Brazil. It is therefore assumed that this repertoire is similar to the speech of other rural areas of the country; moreover, it may be recognised also as Portuguese of the North.